Particle number emission factors from diesel trucks at a traffic intersection: Long-term trend and relation to particle mass-based emission regulation - Yuji Fujitani (Atmospheric Environment: X, 2020)
Particulate matter (PM) in automobile tailpipe exhaust is regulated by PM mass but not particle number (PN) in most parts of the world, including Japan, so the effect of PM mass regulations on the atmospheric PN concentration (PNC) is of interest from the point of view of whether a PNC regulation should be introduced to reduce PNCs. This study examined long-term (2004–2017) monitoring of PNCs and other pollutants at a traffic intersection and other sites in Japan. The decay rate of elemental carbon concentrations at the traffic intersection excellently matched the reductions of PM mass in tailpipe emissions from diesel trucks, indicating that the reduction in atmospheric concentrations directly reflected cleaner vehicle exhausts. Both the reduction of traffic volume and the replacement of older vehicles with newer models that comply with tighter regulations were found to reduce emissions. However, a slower reduction trend was found for exhaust-related PNCs (after excluding photochemically formed aerosols) with particle diameter Dp < 100 nm. The mixed fleet emission factor (EF) on a PN basis (EFPN) (Dp = 10–100 nm) of medium- and heavy-duty diesel trucks during 2005–2016 was estimated to range over 1.1–4.9 × 1014 km−1 veh−1 and 0.5–7.4 × 1014 km−1 veh−1 in winter and summer, respectively, under urban driving conditions (0–50 km h−1). For the EFPN of diesel trucks by regulation year, which was estimated using a combination of traffic data and the positive matrix factorization model applied to environmental data, the EFPN of diesel trucks that meet the 1988–1990 regulation was the highest at 1016 km−1 veh−1 and that of those that meet the latest emission regulation (2009–2010), which requires a diesel oxidation catalyst, a diesel particulate filter (DPF), and a NOx catalyst, was the lowest at 1.4 × 1013 km−1 veh−1. The EFPN of the latest regulation diesel trucks was one order of magnitude lower than that of the mixed fleet EFPN of diesel trucks in 2016. Therefore, when all diesel trucks have been replaced by diesel trucks that meet the latest emission regulation, it is expected that the atmospheric PNC will be reduced by one order of magnitude. However, the EFPN of the latest regulation diesel trucks obtained from environmental data was two orders of magnitude higher than the limit value of the Particulate Measurement Programme regulation for non-volatile particles when comparing at the same emission level of PM mass. Further, since all diesel trucks that meet the latest emission regulation are equipped with a DPF, most of the non-volatile particles should be removed from the exhaust by the DPF. Therefore, the condensable particles and their precursors such as semi-volatile compounds are expected to be the cause of this gap; thus, these control policies are needed to further reduce the vehicle-exhaust-derived PN in the environment. Keywords: Nanoparticle, Ultrafine particle, Particle number concentration, Diesel truck, Traffic intersection, Emission factor